Population pharmacokinetic model of high-dose methotrexate in Chinese patients with intracranial germ cell tumors - Zhao, Jiashu; Wu, Ruoyun; Zhang, Sitian; Lu, Qian; Wang, Ruitao; He, Yingjun; Zhao, Zhigang; Mei, Shenghui (Frontiers in Pharmacology, 2025)
This study aims to investigate the pharmacokinetics of methotrexate (MTX) in Chinese patients with intracranial germ cell tumors (iGCTs) and to develop a robust population pharmacokinetic (PPK) model. A two-compartment model with an exponential inter-individual variability and a proportional residual model was established using nonlinear mixed-effects modeling. The model was based on 5,470 plasma concentration data points from 505 Chinese iGCT patients, including 370 children. The impact of covariates on model parameters was evaluated using forward addition and backward elimination strategies. Goodness-of-fit plots, bootstrap, visual predictive check and normalized prediction distribution errors were used to assess model performance. In the final model, the clearance of the central compartment (CL) was determined using the following equation CL=12.88×eGFR/102.20.23×BW/470.39×eBLM×TBIL/15.3−0.05×ALB/40.9−0.18 (BLM = 0.08 when combined with bleomycin, otherwise = 0). The apparent volume of the central compartment (Vc) was Vc=72.04×BW/470.31. The apparent volumes of the peripheral compartments (Vp) and the inter-compartmental clearance (Q) were fixed as 94.94 L and 1.08 L/h, respectively. Co-administration with bleomycin could increase MTX CL by a factor of 1.08. Elevated total bilirubin and albumin levels were associated with decreased MTX CL. Goodness-of-fit and model evaluation confirmed the final model’s adequacy, stability, and predictive performance. In our study, a PPK model was developed to identify the key factors influencing MTX pharmacokinetics, thereby optimizing and personalizing MTX therapy for Chinese patients with iGCTs.